2013
DOI: 10.1002/j.0022-0337.2013.77.5.tb05510.x
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of Holistic Teaching and Its Effects on Dental Student Learning at University of Bergen, Norway

Abstract: The curriculum of the dental faculty at the University of Bergen, Norway, was revised and a new curriculum implemented in 1998 based on the principles of holistic teaching and patient-centered treatment. The irst candidates graduated in 2003. The change of curricula, experience gained, and lack of an evidence base for holistic teaching justify a general discussion of all relevant aspects associated with this approach. The purpose of this article was to make a contribution towards such a discussion. A PubMed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The findings of this study should be interpreted with caution, since the student's perceptions do not constitute solid evidence about the effectiveness of a curriculum; instead, they are only one of many outcome measures that can be applied for this purpose . This study compared a curriculum that has been implemented for many classes of students (OC) to a curriculum that has been implemented in one class of students (NC).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The findings of this study should be interpreted with caution, since the student's perceptions do not constitute solid evidence about the effectiveness of a curriculum; instead, they are only one of many outcome measures that can be applied for this purpose . This study compared a curriculum that has been implemented for many classes of students (OC) to a curriculum that has been implemented in one class of students (NC).…”
Section: Discussionmentioning
confidence: 97%
“…As noted by Berge et al, these two opposing educational approaches exist more in the form of ideas and intentions rather than being documented in terms of practical effectiveness. Prosthodontics is a field of dentistry where the idea of holism could be appropriately implemented …”
Section: Discussionmentioning
confidence: 99%
“…As for the second statement regarding lack of time, this might be overcome by reducing number of secondary competencies and allowing our students to designate more time, knowledge and efforts for the treatment of comprehensive cases. One study in University of Bergen, revealed that the holistic approach did not improve student's satisfaction with teaching [10]. Their student comments were related to the teaching staff numbers, commitment as well as lack of calibration regarding evaluation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade comprehensive educational approaches have received great attention in both medical and dental academic elds [10]. Most of dental schools have felt the need and importance to change their model of teaching from a subject speci c approach to a more holistic approach that results in an evidence-based quality of oral health care.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, comprehensive educational approaches have received great attention in both medical and dental academic fields [ 10 ]. Most dental schools have felt the need and importance to change their model of teaching from a subject-specific approach to a more holistic approach that results in an evidence-based quality of oral health care.…”
Section: Introductionmentioning
confidence: 99%